2021
DOI: 10.1111/liv.14937
|View full text |Cite
|
Sign up to set email alerts
|

Glecaprevir/pibrentasvir for 8 weeks in patients with compensated cirrhosis: Safety and effectiveness data from the German Hepatitis C‐Registry

Abstract: Glecaprevir/pibrentasvir, a pangenotypic, direct‐acting antiviral combination approved for chronic hepatitis C virus treatment, has limited real‐world evidence supporting 8‐week therapy in compensated cirrhosis. We investigated effectiveness and safety of 187 hepatitis C virus‐infected, treatment‐naïve, patients with compensated cirrhosis receiving 8‐week glecaprevir/pibrentasvir therapy in the German Hepatitis C‐Registry between 2 August 2017 and 1 January 2020. Sustained virologic response was 98.4% (127/129… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…Patients in subgroups of interest such as those with low platelets or with high FibroScan, FIB-4 index, or APRI scores had similar rates of SVR12, supporting the use of 8-week therapy in patients with CC. The favorable safety profile of G/P in this real-world cohort was consistent with that reported in previous clinical trials and real-world studies of G/P for patients with CC [ 8 , 12 ], including EXPEDITION-8, where no serious drug-related AEs or discontinuations due to AEs were reported [ 9 ]. Furthermore, the high SVR12 rates observed in patients traditionally considered as being underserved are in line with the findings from studies which have demonstrated that G/P treatment was highly effective in patients with substance abuse and psychiatric comorbidities [ 13 , 14 , 17 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Patients in subgroups of interest such as those with low platelets or with high FibroScan, FIB-4 index, or APRI scores had similar rates of SVR12, supporting the use of 8-week therapy in patients with CC. The favorable safety profile of G/P in this real-world cohort was consistent with that reported in previous clinical trials and real-world studies of G/P for patients with CC [ 8 , 12 ], including EXPEDITION-8, where no serious drug-related AEs or discontinuations due to AEs were reported [ 9 ]. Furthermore, the high SVR12 rates observed in patients traditionally considered as being underserved are in line with the findings from studies which have demonstrated that G/P treatment was highly effective in patients with substance abuse and psychiatric comorbidities [ 13 , 14 , 17 ].…”
Section: Discussionsupporting
confidence: 87%
“…A few real-world studies have evaluated G/P in patients with CC, with a special interest in harder-to-treat groups such as those with comorbidities, those with HCV GT3 infection, people who use drugs (PWUD), those with a psychiatric disorder, and those with other barriers to treatment [ 11 14 ]. These studies have shown that SVR12 rates with G/P remain high and ≥ 98% in the PP population of GT1–6 patients [ 11 , 12 , 15 ]. Although these data showed G/P was well tolerated and led to high SVR12 rates, potential barriers to successful treatment, such as the presence of comorbidities and patients with other risk factors, may not always be well represented in registrational trials.…”
Section: Introductionmentioning
confidence: 99%
“…In one meta-analysis, involving 12,531 adults treated with G/P from 18 real-world reports [15], only 362 were cirrhotic. The recent German Hepatitis C-Registry report [24] was the largest to date, reporting the effectiveness and safety of 187 patients with compensated cirrhosis, who received the 8-week GLE/PIB therapy. The SVR was 98.4% (127/129) in the PP analysis and 85.8% (127/148) in the ITT analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In this multiple-center cohort study of mixed-genotype or genotype-undetermined HCV-infected patients receiving pan-genotypic DAA therapy, we found an overall SVR rate of 96.5% via PP analysis in a real-world setting. Despite the well-known treatment efficacy of these pan-genotypic DAAs in their landmark clinical trial setting [ 24 , 25 , 26 , 27 ], data on the effect of DAA treatment for these less frequently encountered HCV genotype populations are scarce [ 17 , 28 , 29 ]. In this study, we attempted to fill this knowledge gap on the DAA treatment of infection and demonstrated that the pan-genotypic DAA with either SOF/VEL or GLE/PIB are effective and safe for these patients in the real-world setting.…”
Section: Discussionmentioning
confidence: 99%